Implementation of Civil Servant Discipline Policy in The Office of Women's Empowerment and Child Protection Of Minahasa Regency - Lantang, Daine; Masengi, Evi Elvira; Kandou, Selpius (Technium Social Sciences Journal, 2024)
Discipline for employees who work for the Government, namely Civil Servants, absolutely requires regulations regarding discipline which serve as guidelines for disciplining employees. Disciplinary Regulations create order in the work environment to encourage employees to compete in improving performance to be more productive in order to realize the implementation of government and development tasks. The aim of this research is to find out, analyze, and describe the implementation of the Civil Servant Discipline Policy in the Minahasa Regency Women's Empowerment and Child Protection Service based on PP Number 94 of 2021 concerning Civil Servant Discipline. This research uses a descriptive qualitative method with data collection techniques, namely observation, interviews, and documentation, with data analysis techniques and drawing conclusions. The research results show that the work discipline of civil servants in the Minahasa Regency Women's Empowerment and Child Protection Service is not yet optimal because there are still employees who violate the rules in accordance with the applicable regulations regarding the limits on starting and leaving office hours. There are employees who still do not understand the Job Desk in accordance with the Main Duties and Functions, procrastinate on the work they are given, and there is a lack of sanctions given by their superiors. Factors that hinder civil servant discipline are leadership factors and factors from the employees themselves in the form of employee quality and mentality and lack of socialization of the implementation of these government regulations.